Critical heat flux density in diphasic thermosyphons; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Ponomarev K. O. Konstantin Olegovich (2017, 2017)
Title screen